Survey the Effect of Virtual Network on the Knowledge and Clinical Skills of Surgical Technologist Students - sedighe hannani; nazanin sarraf shahri; asma feizy dehkharghani; najme samii; azar arab khazaie; azin arab khazaie; kiarash kamboozia (Tehran University of Medical Sciences, 2023)
Background and Aim: Virtual networks have become one of the most influential tools in people's lives, affecting various aspects of life. In medical sciences, with numerous advancements, the use of virtual networks is increasing. However, virtual networks can lead to wastage of students' time and a reduction in study hours, which negatively impacts their knowledge and practical skills. Therefore, this study aimed to investigate the impact of using virtual networks on the knowledge and practical skills of surgical technologist students. Materials and Methods: This descriptive-analytical study was conducted on 60 students in the 6th and 8th semester of operating room technology at Iran University of Medical Sciences in 2020-2021. At the end of the semester, the students underwent a comprehensive 40-question theoretical exam to assess their theoretical knowledge. To evaluate the level of virtual network usage, the students filled out a researcher-designed questionnaire. The practical skills of the students were measured based on their internship grades. Normality of the data was assessed using the Kolmogorov-Smirnov, and Pearson correlation coefficient test. Data analysis was performed using SPSS software. Results: According to the findings of this study, there was a significant negative relationship between the level of virtual network usage and theoretical knowledge (P<0.05). This means that with an increase in virtual network usage, the level of students' knowledge decreased. On the other hand, there was a significant positive relationship between theoretical knowledge and practical skills. This means that as the scores of the comprehensive exam increased, the scores of practical skills (internship) also increased. However, no significant relationship was found between the level of virtual network usage and students' practical skills (P>0.21). Conclusion: Based on the findings of this study, virtual networks lead to a weakening of students' theoretical knowledge, as evidenced by the decrease in scores on the researcher-designed questionnaire (level of virtual network usage) and the comprehensive exam scores. Another result of the study was the significant positive relationship between theoretical knowledge and practical skills, indicating that as the comprehensive exam scores increased, the scores obtained in internships also increased.